Dynamic evolutionary patterns of high-temperature steam seepage and thermal strains of coals during heat injection - Zhiqiang LI; Ningchao ZHANG; Jinsheng CHEN; Liwei CHEN; Wenxiang FENG; Longwei LIU; Yungang WANG (Meitian dizhi yu kantan)
Background Thermal stimulation of coal seams using high-temperature steam is recognized as a highly promising technology used to increase gas production. Steam permeability serves as a critical parameter for characterizing the injection capacity of thermal fluids. However, the seepage patterns and evolutionary mechanism of steam in coals remain unclear, and exploring these issues holds critical scientific significance for gas production enhancement via heat injection. MethodsThrough experiments on the seepage and thermal strains of coals during the injection of high-temperature steam performed using the steady-state method, this study investigated the dynamic time variation patterns of the steam permeability and thermal strains of coals. Based on the theories of the Kelvin equation for capillary condensation, slug flow, and thermal stress, this study analyzed the evolutionary mechanisms behind the condensation-induced phase transition and pulsating seepage of steam in coals and behind the thermal strain of coals. ResultsThe experimental results indicate that during the injection of high-temperature steam into coals, the liquid-measured permeability of steam showed an intermittent pulsating pattern with an increase in the heat injection time. A higher steam temperature corresponded to a decreased pulsating peak, a shortened pulsating cycle, and more intense pulsation. During heat injection, the radial and volumetric strains of coals exhibited two to three stages of expansion. The axial strain was manifested as compressive strain under lower steam temperatures and shifted to expansion strain under higher steam temperatures. ConclusionsThe equilibrium pressure of steam in the micropores of coals is below the saturated vapor pressure in a large space. A smaller pore size is associated with a lower pressure required for steam condensation and higher susceptibility to condensation-induced phase transition. The gas-liquid slug flow generated by steam in coals is identified as the main cause of the intermittent pulsation of steam permeability. Additionally, the inward and outward expansion effects are superimposed onto the influence of high-temperature steam on the permeability of coals, leading to decreased steam permeability of macropores but increased steam permeability of small pores within the matrix. During steam injection, the rapid expansion strain in the early stage is primarily dictated by pore pressure, while the slow expansion strain in the middle and late stages is predominantly subjected to the thermal strain induced by a temperature rise. The results of this study will provide a factual basis and theoretical reference for the engineering and numerical simulation of gas recovery via steam injection.